2022
DOI: 10.1002/tesq.3137
|View full text |Cite
|
Sign up to set email alerts
|

Aural single‐word and aural phrasal verb knowledge and their relationships to L2 listening comprehension

Abstract: This study quantifies second language (L2) knowledge of aural single words and aural phrasal verbs (PVs) and investigates their relationship with L2 listening comprehension. An aural first language (L1) meaning recall test format was used to measure knowledge of 81 single-word and 81 PV target items (with equivalent frequencies of occurrence) among 224 Chinese tertiary-level learners of English as a Foreign Language (EFL). Participants' L2 listening was measured with a version of the Test of English for Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 47 publications
7
26
0
Order By: Relevance
“…As a result, vocabulary researchers of the past decades had to correlate orthographic vocabulary knowledge with listening comprehension (Teng, 2016;Staehr, 2008Staehr, , 2009Qian, 2002). Such a practice has received heavy criticism (Cheng et al, 2022;Ha, 2021aHa, , 2021b as researchers believe that aural vocabulary knowledge is a more appropriate predictor of L2 listening than word knowledge measured by tests of orthographic vocabulary knowledge (Cheng & Matthews, 2018;Lange & Matthews, 2020).…”
Section: Receptive Vocabulary Knowledge and Its Relationship With Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, vocabulary researchers of the past decades had to correlate orthographic vocabulary knowledge with listening comprehension (Teng, 2016;Staehr, 2008Staehr, , 2009Qian, 2002). Such a practice has received heavy criticism (Cheng et al, 2022;Ha, 2021aHa, , 2021b as researchers believe that aural vocabulary knowledge is a more appropriate predictor of L2 listening than word knowledge measured by tests of orthographic vocabulary knowledge (Cheng & Matthews, 2018;Lange & Matthews, 2020).…”
Section: Receptive Vocabulary Knowledge and Its Relationship With Com...mentioning
confidence: 99%
“…It is axiomatic that second language (L2) listening and reading comprehension play a crucial role in a person's social functioning as well as academic and professional success. These quintessential language skills involve a complicated set of linguistic and non‐linguistic constituents (Cheng et al., 2022; van den Bosch et al., 2020). Among these various linguistic components, vocabulary knowledge has long been believed to be the most important factor, and the link between vocabulary knowledge and comprehension has always been the center of attention in the literature (McLean et al., 2020; Raeisi‐Vanani & Baleghizadeh, 2022; Stewart et al., 2021; Zhang & Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, strong criticisms have been raised concerning the four-option, multiplechoice test format for the strategic or even blind guessing effects (Stewart et al, 2021;Stoeckel et al, 2021), and the six-option, matching format for issues regarding local item dependency (Ha, 2022c;Kamimoto, 2014). A general conclusion that most of the mentioned authors have agreed on is the endorsement of the meaning-recall format, the format where learners have to manually demonstrate their word knowledge through either L1 translation or explanation (Cheng et al, 2022;Ha, 2022c;Stewart et al, 2021;Stoeckel et al, 2021). However, as Nation and Coxhead (2021) discusses in their Chapter 9, each test format has its pros and cons, and is therefore only optimal for a particular purpose or circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it would not be realistic to suggest a one-size-fit-all test of vocabulary knowledge. Fortunately, there are two tests of receptive, phonological vocabulary knowledge available in the field that employ both the meaning-recognition (McLean et al, 2015) and meaning-recall (Cheng et al, 2022) formats. Teachers of English are encouraged to consult Nation and Coxhead (2021) and other papers cited to decide which of these two mentioned tests are more appropriate for their testing purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It would have been more suitable to have administered the vocabulary assessments in an aural format rather than a written format (e.g., Ha, 2021Ha, , 2022b; however, this route would have also introduced other potential confounding variables (e.g., pronunciation or accent of the language spoken on the test). As research has found a link between aural single-word knowledge and L2 listening comprehension (Cheng et al, 2022), future research should look carefully into the possibility of adapting and validating existing listening vocabulary levels tests for assessing L1-Chinese learners' existing English vocabulary knowledge (e.g., McLean et al, 2015;Ha, 2021, Ha, 2022a. In addition, researchers should consider development of novel incidental vocabulary acquisition tests with spoken language that would be considered as intelligible to the targeted population of students.…”
Section: Discussionmentioning
confidence: 99%